Microfiltration and UV-treatment of Philippine coconut "Buko" (Cocos nucifera Linn.) water - Gubuan, Leonor Felisa T.; Acevedo, Teresita P. (2006)
Aseptic collection of coconut water (CW) from its shell was established and the effects of microfiltration and UV treatment on the physico-chemical, microbiological, sensory properties and peroxidase activity were analyzed immediately after processing and during storage at 4C. Color analysis and volatile flavor components on the other hand were determined one day after processing. Analysis of the former was also continued during storage. Processing by microfiltration and UV treatment resulted to lower Total Plate Count, Coliform and Yeast and Mold Count. Escherichia coli count was negative in all samples. Physico-chemical analyses did not show a consistent pattern in all samples while color change noted a change from transparent to pink in filtered (F), UV treated (U) anf filtered UV (FU) treated samples. Control sample (C) on the contrary changed from transparent to opaque during spoilage. The effect of processing on peroxidase (PO) activity was also investigated and showed that the higher the PO activity, the longer the shelf-life of (CW) as indicated by (F), (U) and (FU) samples. Finally to evaluate the general acceptability of CW, sensory analysis was conducted which revealed the preference for (U) after processing but during storage, (C) was preferred over all samples and (F), the least preferred. Preference for (C) during storage might be attributed to the presence of dodecanoid acid, one of the major fatty acids of fresh coconut water which was absent in (F), (U), and (FU) samples.
"April 2006."
Thesis (M.S. Food Science)--University of the Philippines, Diliman.
Keywords: Coconut water -- Philippines -- Batangas; Coconut water -- Purification -- Filtration -- Philippines -- Batangas; Coconut water -- Purification -- Ultraviolet treatment -- Philippines -- Batangas